2017
DOI: 10.4253/wjge.v9.i3.105
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal solutions to bariatric surgery complications: A review with a focus on technical aspects and results

Abstract: Obesity is a growing problem in developed countries, and surgery is the most effective treatment in terms of weight loss and improving medical comorbidity in a high proportion of obese patients. Despite the advances in surgical techniques, some patients still develop acute and late postoperative complications, and an endoscopic evaluation is often required for diagnosis. Moreover, the high morbidity related to surgical reintervention, the important enhancement of endoscopic procedures and technological innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 168 publications
(185 reference statements)
0
74
0
Order By: Relevance
“…For early leaks percutaneous drains placed either by surgery or interventional radiology may be an option. However, in delayed leaks, endoscopic internal drainage is gaining traction especially in a well circumscribed fluid collection [22,23].…”
Section: Internal Drain Vacuum Therapy Septotomymentioning
confidence: 99%
“…For early leaks percutaneous drains placed either by surgery or interventional radiology may be an option. However, in delayed leaks, endoscopic internal drainage is gaining traction especially in a well circumscribed fluid collection [22,23].…”
Section: Internal Drain Vacuum Therapy Septotomymentioning
confidence: 99%
“…Most authors have reported the use of this test, although the drain is sometimes removed before the fistula has been diagnosed. This diagnostic method can be useful only when the result is positive, since a negative finding does not exclude the possibility of a fistula [13,14].…”
Section: Methylene Blue Testmentioning
confidence: 99%
“…An intraoperative photo showing the first stapler with a black cartridge applied around 5 cm from the pylorus.(Fig. 2)[14,16].STEPS FOR MINIMIZING THE OCCURRENCE OF POST-LSG LEAKAGEMany studies conclude that different techniques may play an important role in the possibility of decreasing post-LSG leakage. These techniques are as follows: use a bougie size of ≥40 Fr; begin the gastric transection 5-6 cm from the pylorus ; use suitable cartridge colors from the antrum to the fundus; reinforce the staple line with a buttress material; follow a proper staple line; remove the crotch staples; preserve proper traction on the stomach before firing; stay away from the Angle Of His by at least 1 cm; check the bleeding from the staple line; and perform…”
mentioning
confidence: 99%
“…For many years, the standard techniques to endoscopically access the pancreaticobiliary region for diagnostic or therapeutic reasons have been enteroscopy-assisted ERCP (e-ERCP) and laparoscopy-assisted ERCP (l-ERCP). [45] The main limitations of e-ERCP include required proficiency at enteroscopy, long procedure time required to reach the ampulla, technical success of only 50%, and limited ERCP accessories that are appropriate for use with an enteroscope. [5] In addition, repeat e-ERCP is time-consuming as accessing the ampulla through deep enteroscopy remains challenging.…”
Section: Introductionmentioning
confidence: 99%